B Group Vitamin Levels in Patients With Chronic Obstructive Pulmonary Disease and The Relation Between Pulmonary Functions - Kirkil, Gamze; Muz, Mehmet Hamdi (Aves, 2008)
Introduction: We aimed to evaluate the B group vitamin levels in patients with COPD and to determine the relationship between vitamin levels and pulmonary functions. Material and Method: Fifty four patients with COPD, who were initially diagnosed during the admission to the outpatient clinic, were studied. Pulmonary function tests and assays of vitamins of COPD patients, healthy subjects were evaluated. Results: All the B group vitamin levels were lower in the COPD group. B1, B2, B12 vitamin levels correlated with smoking (pack/year) (r=-0.33, r=-0.265, r=-0.483, respectively, p<0.05 for all values), forced expiratory volume in one second (FEV1) (r=0.372, r=0.474, r=0.777 respectively, p<0.05 for all values), and FEV1/forced vital capacity (FVC) (r=0.418, r=0.430, r=0.787 respectively, p<0.05 for all values). B6 vitamin levels correlated with FEV1/FVC values (r=0.290, p<0.05). Conclusion: This study confirms a decreased level of B group vitamins in patients with COPD. It may be suggested that B group vitamin supplementation may have a beneficial effect on oxidant/antioxidant imbalance in such patients. Future work is needed to explore the possible relationship between the intake of B group vitamins, systemic and local pulmonary assessment of antioxidant capacity/antioxidant molecules, and lung function.
Keywords: B group vitamins; COPD; antioxidants; pulmonary functions